Development of Dekstop Based Customer Data Information System (Case Study: PDAM Tirta Fulawan Siemeulue Barat) - Rafi Moerdani (International Journal Software Engineering and Computer Science (IJSECS), 2021)
The purpose of this research is to find out and information systems that are running at PDAM Tirta Fulawan, West Simeulue District, and to create an application for customer data management, payment, and meter installation to simplify and speed up the data collection process. From the results of research and observations that have been carried out at PDAM Tirta Fulawan, West Simeulue District, it can be concluded that with this customer information system in PDAM Tirta Fulawan, West Simeulue District, information becomes precise and accurate, especially in the service section, and to obtain information These customers become easier, this information system is able to solve problems that often occur in PDAM Tirta Fulawan, West Simeulue District, namely it is difficult to control and supervise customer data and account payments which can avoid delays in making reports every year and for a certain period, and the creation of a system program information in order to obtain quality information.